Japanese mirror : heroes and villains of Japanese culture heroes and villains of Japanese culture - Buruma, Ian. (Middlesex, Eng., 1985)
In this captivating and marvellously eloquent book, lan Buruma turns to the popular heroes of films, comics, theatre and television as the archetypes of the Japanese as they imagine themselves to be, and as they would like themselves to be'. Combining vivid examples with frank and perceptive analysis, he looks at the dual status of women as both goddesses and she-devils, at the significance of artificiality and transvestism, at the role of the samurai and the gangster, and at the modern father-figure as an object of ridicule. The result is a superb portrait of a fascinating society - and one which removes the enigma attached to Japanese life.
Keywords: Culture